Students’ experiences and expectations of technologies: An Australian study designed to inform planning and development decisions - Gosper, Maree; Malfroy, Janne; McKenzie, Jo (Australasian Journal of Educational Technology, 2013)
The pace of technological change accompanied by an evolution in social, work-based and study behaviours and norms poses particular challenges for universities as they strive to develop high quality and sustainable technology-rich learning environments. Maintaining currency with the latest advances is resource intensive, hence the costs incurred in upgrading existing and introducing new technologies need to be carefully weighed up against the potential benefits to students. This calls for a multidimensional approach to planning, with the student voice being an important dimension. Three Australian universities have recently completed a project to gain a better understanding of students' experiences and expectations of technologies in everyday life and for study purposes. The LMS and 25 other technologies ranging from established university offerings (email, learning management systems) to freely available social networking technologies (YouTube, Facebook) were surveyed. More than 10,000 students responded. This paper discusses the development of the survey and presents the broad trends that have emerged in relation to the current use of technologies and desired future use of these for learning purposes. The implications of the survey findings for developing institutional infrastructure to engage students and support their learning are highlighted.